Prioritizing Local Authorities Effective to Lower the Nationwide PM2.5Concentrations and the Personal Exposure Based on the Source Apportionment with the CAPSS 2016 Emissions Inventory - Bae, Changhan; Kim, Eunhye; Yoo, Chul; Kim, Hyung Chun; Kim, Young Min; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
We quantitatively estimated the PM2.5contributions of SO2, NOx, NHx, VOC, and Primary PM2.5(PPM2.5) emissions released from the local authorities in South Korea for 2016. The Comprehensive Air Quality Model with extensions (CAMx) equipped with the Particulate Source Apportionment Technology (PSAT) was applied to simulate the concentrations and contributions of the criteria air pollutants. The self-contributions and the rest domestic contributions to the annual mean PM2.5concentrations in the local authorities ranged from 0.2 to 18.0 μg/m3(average: 1.7 μg/m3), and 1.9 to 14.5 μg/m3(average: 7.1 μg/m3), respectively. The top-10 local authorities (Dangjin, Pohang, Incheon, Gwangyang, Ulsan, Seoul, Seosan, Boryeong, Yeosu, Taean) that show the highest nationwide PM2.5contributions accounted for 35% of the domestic total contribution. SO2, NOx, and PPM2.5emissions from the top-10 local authorities accounted for 65%, 49%, 31% of the domestic total while production processes, combustion in manufacturing industry, combustion in energy production, and transportation were the dominant emission sources in the areas. It means that selecting the key emission regions and sources at the local authority level would be effective to reduce the PM2.5concentration. Population weighted exposure contribution (PWEC) was also calculated based on the PM2.5contribution and the number of populations by local authorities. Busan, Daegu, and Hwaseong are newly added in the top-10 local authorities that exhibit the highest PWECs in South Korea. Considering that the mobile and non-industrial emissions plays a significant role in increasing the PWEC, more stringent regulations on the transportation and non-industrial emission sectors should be considered to effectively minimize the personal exposure.
Keywords: Contribution; Exposure; Key emission area and sector; PM2.5; Regulation